Revisiting the anatomical basis of varicocele - Samaranayake, U.M.J.E.; Mathangasinghe, Yasith; Malalasekara, Ajith P. (Anatomical Society of Sri Lanka, 2019)
Objective: We intended to revisit aetiology and pathogenesis of varicocele. Results: Several theories were proposed as for the aetiology of left sided varicoceles being commoner than right sided varicoceles such as compression of the left testicular vein by the sigmoid colon, high concentration of adrenaline in the left renal vein causing vasospasms of the left testicular vein, presence of a right angle between the left testicular vein and the renal vein, “nutcracker effect” secondary to a compression of the left renal vein between the superior mesenteric artery and the aorta distal to its confluence with left testicular vein, and the presence of incompetent venous valves of the internal spermatic vein draining the left renal vein causing back flow of the blood. However, these theories were challenged in subsequent studies. Recent studies explored the ultrastructural changes of the pampiniform venous plexus in patients with varicoceles. Histological studies identified changes in the connective tissue density, endothelium and smooth muscle arrangement in these veins. However, the causality of these changes is not yet studied extensively. Genetic studies looking at matrix metalloproteinases synthesis and degradation, inflammation, immune dysregulation or alterations of metabolic pathways are necessary to understand pathogenesis of this clinical entity.
Keywords: varicocele; anatomy; histology; pathology